SISTEM PENJADWALAN MATA PELAJARAN SMK NURUL ISLAM - Yus Jayusman; Indra Maulana Yusup Kusumah (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2015)
Timetable is essential in education. Each of the learning process following the timetable that has been provided in order to avoid conflict when doing the teaching. In practice, there is still a timetable that conflicts with another timetable. Software development method used is the Unified Software Development Process and for modeling using the Unified Modeling Language. As for the manufacture of the interface using Windows Presentation Foundation and to the database using phpMyAdmin. Testing applications is done by using the black box method that consists of Usability test and user satisfaction. The results of this research is a desktop application that serves to draw up the timetable and to prevent clashes between the timetable automatically to complement the features in previous research. The result of the development of applications that Schedule Preparation System Software Lessons in the form of a web application that is used through a web browser. Results of the analysis showed that the quality of the applications developed meet all the standards of quality factors tested